Universities, ethics, and professions [ debate and scrutiny - Barnett, Ronald , 1947-; Jarvis, Peter , 1937-; Strain, John (New York : Routledge, 2009)
Every business and organization needs to impress stakeholders with its ethics policy. This title examines how this emphasis on ethics by the professional world is impacting universities, institutions
Description based on print version record
Includes bibliographical references and index
Keywords: Education, Higher -- Aims and objectives; Education, Higher -- Moral and ethical aspects; Education, Higher